Anti-inflammatory and antioxidant activity of salicylic acid conjugated dihydropyrazoline analogues - Naveen Puttaswamy & , Rekha N D, Lakshmi Ranganatha V, Prashanth T & , Shaukath Ara Khanum (Journal of Applied Pharmaceutical Science, 2018)
Syntheses of substituted salicylic acid appended pyrazoline analogues (7a-j) via 1,3-dipolar cycloaddition were reported earlier. In the present investigation we have performed the anti-inflammatory activity by phospholipase A2 (PLA2) inhibition and in vitro antioxidant activity by 2,2-diphenyl-1-picrylhydrazyl, nitric oxide, hydroxyl radical scavenging assay and ferrous ion chelating assay wherein compounds 7d, 7h, 7i and 7j have shown maximum anti-inflammatory activity. Further, compounds 7d, 7f and 7h were proved to be excellent free radical scavengers.
Keywords: 1,3-dipolar cycloaddition,anti-inflammatory, anti-oxidant,phospholipase A2.